From Sintering to Particle Discrimination: New Opportunities in Metal–Organic Frameworks Scintillators. Issue 1 (31st October 2021) - Villemot, Vincent; Dufour, Nicolas; Mauree, Sharvanee; Sabot, Benoît; Bertrand, Guillaume H. V.; Hamel, Matthieu
Abstract : The characterization of a scintillating metal organic framework (MOF) is not straightforward, mainly due to the small size and low density of the material. In this context, we present herein a generic method to give an easy access to the determination of a key parameter in the scintillation field, namely the light output. To reach this, MOF‐205 was first synthesized as millimetric‐size single crystals then sintered under pressure and temperature conditions to afford a pellet. The density was increased by 300% while maintaining optical properties on par with scintillation application. The as‐prepared scintillator was then characterized in terms of photoluminescence (PL; UV‐excited emission spectrum, time‐correlated single photon counting) and radioluminescence (RL) spectroscopy (beta‐excited emission spectrum, alpha, beta and gamma pulse height spectra, alpha/beta and alpha/gamma discrimination). Results were compared with commercial BC‐404 plastic scintillator performances as well as supported by MCNP6.2 simulation. Abstract : The characterization of a scintillating metal organic framework (MOF) is not straightforward, mainly due to the small size and low density of the material. Herein, a generic method is presented to give an easy access to the determination of the light output, where the key step is the sintering of the MOF.